2013 9th International Symposium on Mechatronics and Its Applications (ISMA) 2013
DOI: 10.1109/isma.2013.6547367
|View full text |Cite
|
Sign up to set email alerts
|

A novel rotation-invariant template matching based on HOG and AMDF for industrial laser cutting applications

Abstract: A new real-time rotation-invariant template matching is proposed for industrial laser cutting applications. The technique is based on Histogram of Oriented Gradients (HOG) algorithm to remove rotational angle before the template matching process. It exploits the HOG and the Average Magnitude Difference Function (AMDF) features for rotationinvariance. Since HOG features are robust against illumination effects, the proposed algorithm is suitable for harsh industrial environments. The final aim of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Traditional template matching generates the similarity map based on pixel intensity values, and is not robust to hard matching scenarios such as significant non-rigid deformations of the object, changes in the illumination and size of the target, and occlusion [7]. To address this issue, more distinctive hand-crafted features such as scale-invariant feature transform (SIFT) [8] and histogram of oriented gradients (HOG) [9] can be used instead of the intensity values for robust template matching [10][11][12][13]. However, these features must be extracted by certain manually predefined algorithms based on expert knowledge, and therefore have limited description capabilities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional template matching generates the similarity map based on pixel intensity values, and is not robust to hard matching scenarios such as significant non-rigid deformations of the object, changes in the illumination and size of the target, and occlusion [7]. To address this issue, more distinctive hand-crafted features such as scale-invariant feature transform (SIFT) [8] and histogram of oriented gradients (HOG) [9] can be used instead of the intensity values for robust template matching [10][11][12][13]. However, these features must be extracted by certain manually predefined algorithms based on expert knowledge, and therefore have limited description capabilities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although a similar line of studies is reported in the literature [5,9,13], which * Correspondence: mpeker@nigde.edu.tr employ HOG for shape detection, we are proposing a new hardware-friendly algorithm, which employs AMDF as an effective and easy-to-implement decision module on FPGA. The method uses a set of features extracted from the HOG module, which is later classified by the AMDF module as explained in [14][15][16]. In this paper, we will demonstrate the effective implementation of the proposed method on FPGA for real-time applications.…”
Section: Introductionmentioning
confidence: 99%